Safety and Efficacy of Nonoperative Treatment in Esophageal Perforation Caused by Foreign Bodies. Issue 1 (19th January 2022) - Liao, Foqiang; Zhu, Zhenhua; Pan, Xiaolin; Li, Bimin; Zhu, Yin; Chen, Youxiang; Shu, Xu
Abstract : INTRODUCTION: Esophageal foreign bodies are often treated by endoscopy, but the treatment of esophageal perforation caused by foreign bodies remains controversial. The purpose of this study was to investigate the safety and efficacy of nonoperative treatment of esophageal perforation caused by foreign bodies. METHODS: We retrospectively analyzed 270 patients admitted to our hospital for esophageal perforation caused by foreign bodies from January 2012 to December 2020, all of whom received nonoperative treatment. RESULTS: The mean age of the patients was 56 ± 17 years, and fish bones were the most common type of foreign body. A total of 61.2% of the perforations were in the cervical esophagus. All patients received nonoperative treatment initially, and the foreign body removal rate using endoscopy reached 97%. The perforation healing rate reached 94.8%, whereas 3 patients (1.1%) died during hospitalization. The median (range) duration of hospitalization was 4 days (3–6). Multivariable analysis showed age ≥ 66 years (odds ratio [OR]: 2.196; 95% confidence interval [CI]: 1.232–3.916; P = 0.008), men (OR: 1.934; 95% CI: 1.152–3.246; P = 0.013), and time to treatment (OR: 1.126; 95% CI: 1.027–1.233; P = 0.011) were independent risk factors for infection, whereas the risk of infection was lower when the foreign body type was fish bone (OR: 0.557; 95% CI: 0.330–0.940; P = 0.028). DISCUSSION: Nonoperative treatment is safe and effective for esophageal perforation caused by foreign bodies. Even if perforation is combined with infection, active nonoperative treatment can still achieve a good effect. Early intervention can effectively reduce the risk of infection and improve patient outcomes.